Efficacy and safety of chemotherapy combined with different doses of IL-2 maintenance therapies for acute myeloid leukemia: A protocol for a Bayesian network meta-analysis. Issue 23 (11th June 2021) - Yin, Xuewei; Ding, Yi; Yu, Liming; Guo, Chenchen; Cui, Yanyan; Zhai, Xixi; Wang, Yan; Ding, Shumin; Shen, Mingyue; Li, Zonghong; Xu, Ruirong
Abstract: Background: Acute myeloid leukemia (AML) is the most common malignant tumor of the hematopoietic system, which seriously threatens the lives of patients. Most AML patients have acute onset, severe condition, and poor prognosis. The present study aimed to comprehensively evaluate the effectiveness and safety of chemotherapy combined with different doses of interleukin-2 (IL-2) maintenance treatments in AML by Bayesian network meta-analysis (NMA). Methods: From its inception until October 2021, we will search PubMed, Cochrane Library, CNKI, Embase, and other databases to comprehensively collect randomized controlled trials (RCTs) of chemotherapy combined with different doses of IL-2 maintenance therapies for AML. Two independent researchers will complete the literature screening and data extraction according to the inclusion and exclusion criteria, and then independently conduct a bias risk assessment of all the evidence. Bayesian NMA was used to evaluate all the evidence comprehensively. Use STATA16.0 and WinBUGS1.4.3 software to process and analyze all data, and classify the quality of evidence in NMA according to grading of recommendations assessment, development, and evaluation . Results: The study will evaluate the efficacy and safety of chemotherapy combined with different doses of IL-2 maintenance therapies for AML. Conclusion: The study will provide a basis for the efficacy and safety of chemotherapy combined with different doses of IL-2 maintenance therapies for AML. We hope that this study can provide meaningful support for clinicians and patients. Protocol registration number: INPLASY202140106 Ethical approval: Since the study is based on published or registered RCTs, ethical approval and patient informed consent are abandoned.